Epidemiological Study on Trichomonas Vaginalis Parasite and Estimation of Some Elements and Antioxidants in the Serum of Infected Women in Samarra City: Studi Epidemiologi Parasit Trichomonas Vaginalis dan Estimasi Beberapa Unsur dan Antioksidan dalam Serum Wanita Terinfeksi di Kota Samarra - Hamood , Nibras abud al Aziz (Indonesian Journal on Health Science and Medicine, 2024)
The current study investigates the prevalence of Trichomonas vaginalis in women visiting Samarra General Hospital between August 2023 and June 2024. A total of 325 samples were examined from women aged 19 to 51 years, with an infection rate of 2.34%. The highest infection rate was observed in the 30-40 age group, among women experiencing itching during menstruation (4.16%), those with white vaginal discharge (2.97%), and infertile women (4.16%). The infection rate was higher among rural women (3.57%) compared to urban residents. Regarding trace elements, the study recorded a significant decrease in serum zinc and iron levels in infected women (p < 0.01) compared to the control group. However, no significant difference was observed in lead concentrations, with levels recorded as 2.83 µg/dl and 2.62 µg/dl in infected and control groups, respectively. Additionally, antioxidant levels showed a notable decline in infected women: Catalase (CAT): 6.88 pg/ml Superoxide dismutase (SOD): 15.31 pg/ml Glutathione peroxidase (GPx): 112.9 pg/ml Highlights: Prevalence: 2.34% infection in 325 women, highest in 30-40 age group. Trace Elements: Decreased zinc/iron, no significant lead difference. Antioxidants: Reduced CAT (6.88), SOD (15.31), GPx (112.9) pg/ml. Keywords: Trichomonas vaginalis, prevalence, trace elements, antioxidants, infection rate